A comparison between the 1985 proposed Food and Nutrition Research Institute-Philippine Pediatric Society (FNRI-PPS) and the World Health Organization (WHO) international anthropometric standards in the assessment of nutrition status among preschool children aged 12-72 months - Monte, Rebecca M.
Evaluation of nutritional status by anthropometry is critically dependent not only on the indicator and cut-off values being used, but most importantly on what anthropometric standards, the weights and heights should be compared with. In the Philippines, the newly developed 1985 FNRI-PPS standards have been recommended for use locally. However, WHO recommends the use of the 1978 WHO International standards for both developing and developed countries. The extent of agreement between the 2 standards in categorizing preschool children into different percentile categories of nutritional status as well as the proportion of children who will be diagnosed as malnourished or normal based on the 3 indicators, namely, weight for age, height for age and weight for height were investigated. A comparison of the proportion of children categorized to the different classifications of nutritional status using combined weight and height percentiles was also done. The subjects in this study were 2778 children aged 12-72 months from the municipality of Muntinlupa with 70 coming from government facilities representing the low income bracket, and 30 from private facilities, to represent the middle and high income group. Their mean anthropometric measurements exceeded the P50 values of the FNRI standards but were only slightly above the P3 values of the WHO standards for both weight and height for age. In terms of percentile distribution, the subjects tended to cluster at the P50 to P75 level with slight skewing to the right when using the FNRI standards but was markedly skewed to the left with majority at the P3 to P25 level when using the WHO standards. The results of this study revealed that no agreement at all exists between the 2 standards in evaluating the nutritional status of preschoolers when using weight for age and height for age indicators for all age groups. However, for the index weight for height and using combined weight and height percentile, a small degree of agreement was shown to exist.